Becoming a professional: A longitudinal qualitative study of the graduate transition in BSc Psychology. Issue 2 (25th February 2019) - Reddy, Peter; Shaw, Rachel
Abstract : Purpose: Research into the experience of BSc Psychology students and graduates in the graduate transition was carried out to enquire if ontology is central to educational transformation; if professional work experience is important in the process of becoming; and how graduates experience the transition from student to professional. The paper aims to discuss these issues. Design/methodology/approach: In this qualitative longitudinal in-depth interview investigation four one-year work placement students were interviewed twice and five graduates were interviewed at graduation and again two years later. Student transcriptions were analysed thematically and graduate transcriptions received interpretative phenomenological analysis. Findings: Placement students became legitimate participants in professional life. Graduates thought that BSc Psychology should enable a career and were dissatisfied when it did not. Professional psychology dominated career aspiration. Relationships and participation in work communities of practice were highly significant for learning, personal and professional identity and growth. Practical implications: Ontology may be central to educational transformation in BSc Psychology and is facilitated by integrated work experience. A more vocational focus is also advocated. Originality/value: The UK Bachelor's degree in psychology is increasingly concerned with employability however becoming a professional requires acting and being as well as knowledge and skills and Barnett and others have called for higher education to embrace an ontological turn. This is explored in the context of BSc Psychology student experience and reflection on work placements, graduation and early career development.